Development of a model for decentralized control of a group of collaborative robot manipulators - Maksymova, S.; Shakhov, P. (My University, 2025)
The paper considers an approach to developing a model for decentralized control of a group of collaborative robot manipulators, focused on increasing autonomy, adaptability, and safety in a dynamic production environment. The proposed solution allows minimizing dependence on centralized computing resources, reducing the risks of system failures, and ensuring effective interaction of robots in the joint performance of complex manipulation tasks. The results of the study demonstrate the prospects of decentralized models for implementing the concepts of Industry 5.0.
Keywords: decentralized control; collaborative robot manipulator; multi-agent system